Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/poms.12050
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Per‐Use Rentals and Sales of Durable Products and Their Distinct Roles in Price Discrimination

Abstract: We consider a setting in which consumers experience distinct instances of need for a durable product at random intervals. Each instance of need is associated with a random utility and the consumers are dierentiated according to the frequency with which they experience such instances of need. We use our model of consumer utility to characterize the rm's optimal strategy of whether to sell, rent, or do a combination of both in terms of the transaction costs and consumers' usage characteristics. We nd that the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…It is possible for the leasing channel to be greener if we remove the off-lease products in the mid-life. Gilbert et al (2014) use a per-use rental model of consumers to figure out the firm's optimal strategy. They conclude that the two operation modes played differently in the way to price discrimination.…”
Section: The Leasing Channel and The Selling Channelmentioning
confidence: 99%
“…It is possible for the leasing channel to be greener if we remove the off-lease products in the mid-life. Gilbert et al (2014) use a per-use rental model of consumers to figure out the firm's optimal strategy. They conclude that the two operation modes played differently in the way to price discrimination.…”
Section: The Leasing Channel and The Selling Channelmentioning
confidence: 99%
“…We also add to a small literature that deals explicitly with economic issues relating to peer-to-peer 'sharing economy' marketplaces. For example, (Fradkin 5 Other analysis of secondary markets for durable goods in the literature include aircrafts ( (Gilligan 2004) (Gavazza 2011a) (Gavazza 2011b)), textbooks ((Chevalier and Goolsbee 2009)), digital goods ((Varian 2000), (Rao 2011), (Schiller 2012) (Gilbert, Randhawa and Sun 2013)) among others. There is also a literature in macroeconomics that uses transaction costs to explain the slow adjustment in the stock of durables ( (Eberly 1994), (Attanasio 2000)).…”
Section: Potential Economic Effects Of Peer-to-peer Rentalmentioning
confidence: 99%
“…e model established by Li et al discussed this issue and found that manufacturers offer products to consumers at low prices through leasing, which expands the market coverage and creates price discrimination [4]. Gilbert et al [5] analyzed how per-use rentals and sales differentiate consumers within the framework of a hybrid selling-leasing model. ey found that sales allow a firm to discriminate according to consumers' usage frequencies, and rentals allow it to discriminate according to their realized valuation.…”
Section: Selling Versus Leasingmentioning
confidence: 99%
“…ey also mentioned two interactions between consumers and leases: the decrease in the lease product value and the restrictions on the choice of leasing and selling under capital constraint. Gilbert et al [5] used a similar model to describe the relationship between consumer utility and usage rate. For electronic products, there are differences in consumer acceptance of product leases.…”
Section: Consumers' Preferences For Leasingmentioning
confidence: 99%